2019
DOI: 10.1101/670083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endothelial-derived exosomes demonstrate a link between endothelial innate inflammation and brain dysfunction and injury in aging

Abstract: We test the hypothesis that endothelial cells take on an inflammatory phenotype in functionally intact human subjects with radiographic evidence of white matter injury. Markers within all three complement effector pathways and regulatory proteins were quantified from endothelial-derived exosomes (EDE) of subjects (age 70-82) with (n=11) and without (n=16) evidence of white matter hyperintensity on MRI. Group differences and associations with systemic markers of immune activation (IL6, ICAM1), cognition and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Consistent with this, mouse models show that inflammation has a selective impact on executive functions while sparing memory 19 . Additionally, this finding is supported by observations from other neurological diseases where executive dysfunction is prominent, including both primary autoimmune conditions such as multiple sclerosis and autoimmune encephalitis, as well as other neurodegenerative disorders such as vascular‐related cognitive impairment 6,10,12,47,48 . Many studies have similarly found an association with peripheral markers of inflammation and executive function broadly as well as verbal fluency specifically, although none have reported this finding within the CSF 49–53 .…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Consistent with this, mouse models show that inflammation has a selective impact on executive functions while sparing memory 19 . Additionally, this finding is supported by observations from other neurological diseases where executive dysfunction is prominent, including both primary autoimmune conditions such as multiple sclerosis and autoimmune encephalitis, as well as other neurodegenerative disorders such as vascular‐related cognitive impairment 6,10,12,47,48 . Many studies have similarly found an association with peripheral markers of inflammation and executive function broadly as well as verbal fluency specifically, although none have reported this finding within the CSF 49–53 .…”
Section: Discussionmentioning
confidence: 72%
“…19 Additionally, this finding is supported by observations from other neurological diseases where executive dysfunction is prominent, including both primary autoimmune conditions such as multiple sclerosis and autoimmune encephalitis, as well as other neurodegenerative disorders such as vascular-related cognitive impairment. 6,10,12,47,48 Many studies have similarly found an association with peripheral markers of inflammation and executive function broadly as well as verbal fluency specifically, although none have reported this finding within the CSF. [49][50][51][52][53] Moreover, it has also been demonstrated that immune activation alters brain connectivity specifically in the executive network while sparing the default mode network associated with memory as well as the salience network associated with emotional regulation.…”
Section: Csf Pleocytosis Has Been Observed In Many Different Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Complement cascades play an important role in thrombosis and are increased in exosomes released from endothelial cells in individuals with chronic cerebrovascular disease and may be associated with COVID-19-related thrombosis. 55,72 In acute stroke injury, blocking the alternative complement pathway through CR2 (complement receptor 2) inhibition can reduce the robust inflammatory infiltrate into ischemic brain tissue while preserving the ability for opsonins in the classical complement pathway to modulate synaptic pruning and debris clearance. 73 In chronic cerebrovascular disease, steady, low-level inhibition of particular complement cascades could reduce microvascular thrombosis, blood-brain barrier leakage, or both thereby reducing the progression of white matter injury.…”
Section: Inflammation As a Therapeutic Target For Vascular Brain Healthmentioning
confidence: 99%
“…Complement activation is known to play a significant role in human and experimental models of stroke 24 as well as cerebral small vessel disease. 25 Ischemia-induced exposure of neo-epitopes on cerebral endothelium can also trigger complement activation. 26 MASP-2 knockout mice exposed to transient middle cerebral artery occlusions have reduced stroke volumes, improved neurologic outcomes, and reduced C3 deposition in the cortex.…”
Section: Sars-cov-2 Mediated Systemic Hypercoagulability As a Driver Of Strokementioning
confidence: 99%